Analysis of the Effect of World Bank Loans, Foreign Direct Investment (FDI), Government Spending, and Economic Growth on Stock Market of ASEAN Countries in 2013-2022 - Prawiradikarta, Annisa Azzahra Herawan; Suripto, Suripto; Harori, M. Iqbal (The Es Economics and Entrepreneurship, 2025)
This study aims to determine the effect of World Bank loans, Foreign Direct Investment (FDI), government spending, and economic growth on Stock Market performance in ASEAN countries for the period 2013-2022. Using the type of explanatory research with a quantitative approach, from secondary data obtained through literature studies and documentation studies with the Eviews 12 tool. The sample consists of 50 observations from 5 countries selected using purposive sampling technique, namely Indonesia, Thailand, Philippines, Vietnam, and Cambodia using multiple linear regression analysis. The results show partially that World Bank loans, Foreign Direct Investment (FDI), and government spending have an insignificant effect on the Stock Market, while economic growth has a significant effect with a positive relationship. Simultaneously, all four variables have a significant effect with a positive relationship on ASEAN stock market performance. This study suggests considering other variables that have more potential to influence the stock market performance of ASEAN countries.